Analisis Kelayakan Usahatani Madu Kelulut (Trigona sp) di Desa Nanga Kebebu Kabupaten Melawi Provinsi Kalimantan Barat - Muhammad Faisal; Adi Suyatno; Anita Suharyani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
One of the surviving non-animal timber forest products is honey produced by bees (Trigona sp). The cultivation of kelulut honey produces an economic source for the community through the sale of the proceeds from the kelulut honey itself. This is an opportunity for the community to be able to cultivate honey bees in order to improve the welfare of the community. To be able to increase the production of honey kelulut, an analysis of the feasibility of farming is needed. The purpose of this study is to analyze the cost, revenue, income and feasibility of the kelulut honey bee farming business run by farmers in Nanga Kebebu Village. The sample in this study was 35 farmers in Nanga Kebebu Village who met the criteria as analyzed by researchers. The method in this study is included in quantitative descriptive research. Farm feasibility analysis to calculate cost, revenue, revenue, BEP and R/C Ratio. The results of the analysis show that the kelulut honey farming business in Nanga Kebebu Village is feasible to be cultivated with an average yield of farmers' net income of Rp. 16.033.671/ farmer / year, with an average receipt of Rp. 21,771,429 / farmer / year and an average cost of Rp. 5.737.757/ farmer / year, production yield of 54 liters / year > BEP production of 0,76 liters / year. Furthermore, the selling price is IDR 400,000 / liter > BEP the price is IDR 304.402/ liter. While the R/C result is 3,79. Kata kunci: Non-timber forest products, Farming feasibility, Honey Bee.